Dampak Kelelahan Mental (Burnout) Terhadap Kinerja Karyawan Retail Besi dan Baja - Yulfanani Alfajar; Roziana Ainul Hidayati (Universitas Muhammadiyah Gresik, 2022)
Decrease in employee performance cause of burnout due to doing more than one type of work and responsibilities at one time. This study aims to understand burnout (mental fatigue) that is often experienced by employees and the factors that cause it. So that this research can be a reference for readers who experience or want to know burnout. This research was conducted with a qualitative descriptive research method based on the results of observations and interviews with resource persons in the field and continued the results of previous research. The type of sample used in this research is simple random sampling. The sample in this study were employees and employees of Iron and Steel Retail who found a double job desk (holding more than one task and responsibility). This study shows the impact of mental fatigue experienced by employees due to carrying out several different tasks and responsibilities. These include decreased loyalty, decreased productivity, and job discomfort. Mental fatigue occurs due to the severe stress experienced by a person in carrying out activities, resulting in a feeling of reluctance or not being motivated to carry out activities that are usually done. The results of this study can be used as a reference for managing human resources (employees) in companies to create work comfort and improve the quality of employees' work. This research is limited to company x, for development it is necessary to carry out more in-depth research and involve many companies and employees as the population.